Who have been the most harmed by the crisis? Evidence from Spain - García-FERNANDEZ, Rosa María; Llorca-RODRIGUEA, Carmen Maria (Journal of Economics and Political Economy, 2015)
The aims of this research are to assess the initial impact of the current economiccrisis on poverty and social exclusion in Spain and to identify the most vulnerable sectors of society. We apply Probit models to Spanish Income and Living Conditions Surveys of 2007 and 2009 to analyze income poverty and financial functionings of basic material deprivation linking pecuniary and health aspects. Our results show an increment of poverty, above all, extreme poverty, and a worsening of the deprivation risk not only for those with a weaker position in the Spanish labour-market, butfor employers and self-employed, as well.In addition, we found changes in risk factors such as educational leveland age. These findingsshould be taken into account when designing the regulatory reforms of social policies and labour market regulations.